Exploring Early Childhood TeacherÔÇÖs Understanding of Numeracy Literacy at Raudhatul Athfal - Lathifatul Fajriyah; Latifatul Muawanah; Atika Ayu Rissa (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Early childhood numeracy skills are important competencies for children, because these skills not only include problem-solving skills but also the application of mathematical concepts in everyday life. This study aims to explore teachers' understanding of numeracy literacy learning in early childhood at Raudhatul Athfal. This study uses a descriptive qualitative approach, the collection method uses semi-structured interviews developed based on PAUD teacher competency indicators and observations are carried out in a participatory manner using observation sheets containing indicators of literacy and numeracy learning activities. The analysis process begins with reducing data from the interview results to simplify the data so that it is easy to understand and analyze. Furthermore, the coding process is carried out to classify the data into main themes, then represent patterns in teacher perceptions and practices in literacy and numeracy learning. To ensure data validity, researchers apply data triangulation and checking with colleagues. The results of the study indicate that teachers do not yet have adequate competence in teaching literacy and numeracy. There are still challenges in its implementation, such as providing ongoing training, linearizing academic degrees in early childhood education, and facilities and infrastructure in improving teacher quality and learning in the classroom.